Pengaruh Penggunaan Media Audio Visual terhadap Minat Belajar Siswa Pendidikan Agama Kristen (PAK) Kelas VIII SMP Negeri 2 Tarutung Tahun Pembelajaran 2023/2024 - Rotua Gultom; Grecetinovitria M. Butar-Butar; Helena Turnip; Boho P. Pardede; Lince R.T Simamora (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The purpose of this study was to determine the positive and significant influence of the use of Audio Visual Media on the learning interests of Christian Religious Education (PAK) students of class VIII SMP Negeri 2 Tarutung in the 2023/2024 academic year. The method used in this study is a quantitative research method with descriptive statistics. The population was all class VIII students of SMP Negeri 2 Tarutung, totaling 175 people and a sample of 35 people was determined using random sampling techniques or randomly. Data were collected with a positive closed questionnaire of 45 items. The results of the data analysis show that there is a positive and significant influence of the use of Audio-visual Media on the learning interest of students of Christian Religious Education (PAK) class VIII SMP Negeri 2 Tarutung in the 2023/2024 academic year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.426> rtable ( = 0.05, n = 35) = 0.334 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 2.706> ttable ( = 0.05, dk = n-2 = 33) = 2.042 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Ŷ = 14.52 + 0.625. b) Regression determination coefficient test (r2) = 17.2%. 3) Hypothesis testing using the F test obtained Fcount> Ftable, namely 7.32> 1.62. Thus, Ha is accepted and H0 is rejected. Thus, it can be seen that the research hypothesis proposed by the author is accepted, namely that there is a positive and significant influence between Audio-visual Media on the learning interest of Christian Religious Education (PAK) students in class VIII of SMP Negeri 2 Tarutung in the 2023/2024 academic year.